2017
DOI: 10.1590/1807-1929/agriambi.v21n5p304-309
|View full text |Cite
|
Sign up to set email alerts
|

Flow rate dynamics of pressure-compensating drippers under clogging effect

Abstract: A B S T R A C TThe clogging dynamics of pressure-compensating drippers is still poorly addressed, and its understanding is quite important to control clogging. The aim of this study was to evaluate the flow performance of pressure-compensating drippers under clogging effect. Eight pressure-compensating emitters, model J-SC Jain PC-PLUS with nominal flow rate of 2.2 L h -1 were evaluated. The tests were run for 8 h d -1 for 4 weeks, a total of 160 h. Every 40 h, the concentration and granulometry of suspended p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
1
1
1
2
Order By: Relevance
“…Similar results had been found by Pinto et al [51] for some models of pressure-compensating drippers, behavior attributed to the imbalance of their membrane.…”
Section: Regarding Type Of Emittersupporting
confidence: 89%
“…Similar results had been found by Pinto et al [51] for some models of pressure-compensating drippers, behavior attributed to the imbalance of their membrane.…”
Section: Regarding Type Of Emittersupporting
confidence: 89%
“…Similarly, we found that coefficient of variation computed at an hourly basis was 1.653% (CI 95% 1.240-2.065%) in the control and 3.587% (CI 95% 2.713-6.444%) in the HF-DLF, with scarce differences among dilution, suggesting that accumulation of deposited material in the emitters affected the dripline flow performance. Such coefficient of variation was lower than those found in other similar studies [28,29] and can be marginally acceptable as indicated by Bodole et al [26], according to which a test duration of more than 60 min is enough to minimize the uncertainty due to the initial fluctuation of the data. The lower variation of the HF-DLF is likely due to an anti-clogging shape of the present emitters if compared to other emitters [30].…”
Section: Discussioncontrasting
confidence: 49%
“…In researches that aim to improve the performance of drippers, self-cleaning is considered an alternative that should be explored in drippers design phase to provide emitters less susceptible to clogging [11]. Additionally, when adding clay particles, the flow rate of non-pressure compensating drippers [9] and pressure-compensating drippers [12] has been reported to increase in some test conditions.…”
Section: Manufacturer/model Naandanjain/ Taldrip Naandanjain/ Taldripmentioning
confidence: 99%